2022
DOI: 10.1186/s12978-022-01498-4
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of postpartum hemorrhage and associated factors among women who gave birth in Ethiopia: a systematic review and meta-analysis

Abstract: Background Postpartum hemorrhage (PPH) is the leading cause of maternal mortality and morbidity worldwide, particularly in resource-limited countries such as Ethiopia. Findings from a few studies were inconsistent and inconclusive. Therefore, this study aimed to estimates the pooled magnitude of PPH and factors associated with PPH among women who gave birth in Ethiopia. Methods Electronic databases such as Medline, Pub Med, Cochrane library, the We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…Antecedents of postpartum hemorrhage and multiparity are risk factors for postpartum hemorrhage. Prenatal visits are essential for detecting women at high risk [ 50 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Antecedents of postpartum hemorrhage and multiparity are risk factors for postpartum hemorrhage. Prenatal visits are essential for detecting women at high risk [ 50 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Antecedents of postpartum hemorrhage and multiparity are risk factors for postpartum hemorrhage. Prenatal visits are essential to detecting women with high risk [52].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Postpartum hemorrhage (PPH) is the leading cause of maternal mortality and morbidity worldwide. 1 World Health Organization (WHO) statistics suggested that 60% of maternal deaths in developing countries were due to PPH, accounting for more than 100,000 maternal deaths per year worldwide. 2 Most PPH deaths can be avoided with timely detection and management; however, critical challenges persist.…”
Section: Introductionmentioning
confidence: 99%